Economic development of modern Japan - Nakamura, Takafusa (Ministry of Foreign Affairs, 1985)
This book introduce about economic development, Japan's case an overview. Preliminary conditions and the restoration. Developments up to world war 1. World war 1 and the interwar period (1914 - 1939)